IT-based reminders for medication adherence: systematic review, taxonomy, framework and research directions. Issue 1 (2nd January 2020) - Singh, Neetu; Varshney, Upkar
ABSTRACT: IT-based reminders have been one of the most promising interventions to improve medication adherence. Even with considerable research, it is not clear what types of reminders are effective for different patients and diseases and how much improvement in adherence is sustainable over time. To answer this, we conduct a systematic literature review of IT-based reminders. We utilise a six-step process reflecting the systematicity and transparency which is implemented using PRISMA (P referred R eporting I tems for S ystematic Reviews and M eta-A nalyses). Then, we develop a taxonomy of reminders, using Nickerson's method, including thirteen characteristics categorised in four different dimensions. The findings are used in deciding when and where and how to use reminders with what type of patients for how long in improving medication adherence. The subsequent detailed analysis of the articles brought numerous insights leading to the development of Comprehensive Framework for Medication Reminders (CFMR). The framework can be used by the IS researchers for developing theoretical models to study the effectiveness of interventions for improving medication adherence. The taxonomy can be extended to a multi-level taxonomy using the proposed framework and research directions and can be further evaluated using domain experts.